ANALISIS YURIDIS TINDAK PIDANA KOHABITASI PERSPEKTIF KITAB UNDANGUNDANG HUKUM PIDANA (KUHP) DAN HUKUM PIDANA ISLAM: Juridical Analysis of Cohabitation Criminal Offenses from the Perspective of the Penal Code (KUHP) and Islamic Criminal Law - Ahmad Faissol Akbar; Rafid Abbas (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
In adolescence, or what can be called the threshold of adulthood, there is a high potential for engaging in promiscuity or cohabitation. This is a matter of great concern and anxiety for parents, as well as for society and the state. The type of research method used is normative legal research, utilizing legal material sources that focus on the analysis of legal regulations.The results of this study are as follows: (1)The absence of a legal enforcement system for perpetrators of the criminal act of cohabitation in Indonesia in the past has contributed to the prevalence of such disgraceful acts. However, with the enactment of the new Criminal Code (KUHP), which explicitlycriminalizes this offense, it is expected that community life in Indonesia will become more peaceful and prosperous. (2)Theperspective of Islamic criminal law clearly and strictly prohibits acts of cohabitation, especially for all Muslims in Indonesia, due to therisk of falling into immoral acts and major sins. (3)Both the KUHP and Islamic criminal law equally prohibit the criminal act ofcohabitation, considering the negative impacts that would arise if such actions were allowed to spread unchecked in Indonesia Pada usia remaja atau dapat disebut usia diambang dewasa sangat berpeluang besar terjadinya pergaulan bebas maupun kohabitasi, oleh karena itu hal tersebut yang sangat ditakuti dan dicemaskan orang tua, terlebih masyarakat dan negara. Adapun jenis metode penelitian yang digunakan yakni penelitian hukum Normatif dengan menggunakan sumber bahan hukum yang berfokus pada analisis aturan-aturan hukum. Hasil dari penelitian ini yaitu, 1) Tidak adanya sistem penegakan hukum bagi pelaku tindak pidana kohabitasi di Indonesia sebelumnya yang membuat maraknya tindakan tercela tersebut di Indonesia, tetapi dengan adanya KUHP baru yang secara tegas mengancam tindak pidana tersebut diharapkan kehidupan di lingkungan masyarakat Indonesia menjadi jauh lebih damai dan sejahtera. 2) perspektif hukum pidana Islam yang secara jelas telah melarang keras agar menjauhi tindakan kohabitasi ini khususnya bagi seluruh umat muslim di Indonesia, karena dikhawatirkan terjerumus ke perbuatankeji dan dosa besar. 3) KUHP maupun Hukum Pidana Islam telah sama-sama melarang tindak pidana kohabitasi karena mengingatdampak negatif yang ditimbulkan akibat tindakan tersebut jika terus merajalela di Indonesia.